475OOverall survival (OS) from the AURA3 phase III study: Osimertinib vs platinum-pemetrexed (plt-pem) in patients (pts) with EGFR T790M advanced non-small cell lung cancer (NSCLC) and progression on a prior EGFR-tyrosine kinase inhibitor (TKI). (24th November 2019) - Wu, Y-L; Mok, T S K; Han, J-Y; Ahn, M-J; Delmonte, A; Ramalingam, S S; Kim, S-W; Shepherd, F A; Laskin, J; He, Y; Akamatsu, H; Theelen, W S M E; et al.
Abstract: Background: In AURA3 (NCT02151981), osimertinib, a 3 rd -generation EGFR-TKI, significantly prolonged progressionfree survival (PFS) and improved response rate vs plt-pem in pts with centrally confirmed EGFR T790M advanced NSCLC and progression on a prior EGFR-TKI. Here we report mature OS data. Methods: Adult pts were randomised 2:1 to receive oral osimertinib (80 mg once daily) or intravenous pem (500 mg per m 2 of body surface area) + carboplatin (target area under the curve 5)/cisplatin (75 mg per m 2 ), every 3 weeks, ≤6 cycles. Treatment beyond progression (RECIST 1.1) was allowed if clinical benefit continued. Pts receiving plt-pem could cross over to osimertinib on disease progression. Asymptomatic CNS metastases were allowed. Primary endpoint was investigator-assessed PFS. OS and safety are reported as secondary endpoints. Data cut-off (DCO): 15 March 2019. Results: In total, 419 pts were randomised (osimertinib, n = 279; plt-pem, n = 140); 99 pts (71%) crossed over to osimertinib from plt-pem. At DCO, 188 pts (67%) in the osimertinib arm vs 93 pts (66%) in the plt-pem arm had died, including 66/99 (67%) crossover pts; median OS 26.8 mo (95% confidence interval [CI] 23.5, 31.5) vs 22.5 mo (95% CI 20.2, 28.8) respectively, hazard ratio (HR) 0.87 (95% CI 0.67, 1.12; p = 0.277); survival rate at 24 mo was 55% vs 43% and at 36 mo was 37% vs 30%. Time to first subsequent treatment showed a large, clinically meaningful numerical advantage towards osimertinib, HR 0.21 (95% CI 0.16, 0.28; p < 0.001); time to second subsequent treatment, HR 0.87 (95% CI 0.69, 1.11; p = 0.263). In both arms, 99% pts had any adverse event (AE). Any AE grade ≥3 causally related to study treatment was 9% vs 34% for osimertinib and plt-pem respectively. Most common AEs were diarrhoea, 44% (grade ≥3, 1%), and nausea, 49% (grade ≥3, 4%), with osimertinib and plt-pem respectively. Conclusions: A numerical advantage in OS was observed for pts receiving osimertinib vs plt-pem, with the majority of pts in the plt-pem arm having crossed over to osimertinib. The safety profile of osimertinib remains consistent with previous findings. Clinical trial identification: NCT02151981. Editorial acknowledgement: Laura Crocker, BMedSci, of iMed Comms, an Ashfield Company, who provided medical writing support funded by AstraZeneca. Legal entity responsible for the study: AstraZeneca. Funding: AstraZeneca. Disclosure: Y-L. Wu: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Honoraria (self): Eli Lilly; Honoraria (self): Pfizer; Honoraria (self): MSD; Honoraria (self): Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim. T.S.K. Mok: Honoraria (self): ACEA Pharma, Alpha Biopharma Co., Ltd., Amgen, Amoy Diagnostics Co., LTD., AstraZeneca (before 1/1/19), Bayer, BI, Blueprint Medicines Corporation, BMS, Celgene, CStone Pharmaceuticals, Eli Lilly, Fishawack Facilitate Ltd, Hengrui Therapeutics Inc., Ignyt; Advisory / Consultancy: ACEA Pharma, Alpha Biopharma Co., Ltd., Amgen, Amoy Diagnostics Co., LTD., AstraZeneca (before 1/1/19), Bayer, BI, Blueprint Medicines Corporation, BMS, Celgene, Cirina, CStone Pharmaceuticals, Eli Lilly, Fishawack Facilitate Ltd, geneDecode Co., Ltd. (un; Leadership role: AstraZeneca PLC, Hutchison Chi-Med; Research grant / Funding (institution): AstraZeneca, BMS, Clovis Oncology, MSD, Novartis, Pfizer, Roche, SFJ, XCovery; Shareholder / Stockholder / Stock options: Shareholder: Hutchison Chi-Med, Sanomics Ltd. Stock option: Clearbridge Biomedics (now Biolidics Ltd.), Loxo-Oncology, OrigiMed Co. Ltd., Virtus Medical Group; Full / Part-time employment: The Chinese University of Hong Kong; Officer / Board of Directors: Remunerated: AstraZeneca PLC, Hutchison Chi-Med Non-remunerated: American Society of Clinical Oncology (ASCO) Asian Thoracic Oncology Research Group (ATORG) Chinese Lung Cancer Research Foundation Limited (CLCRF) Chinese Society of Clinical Oncology (CS. J-Y. Han: Honoraria (self): Roche, AstraZeneca, Bristol-Myers Squibb, MSD, Takeda; Advisory / Consultancy: AstraZeneca, Bristol-Myers Squibb, MSD, Takeda, Pfizer, Novartis, Lilly; Research grant / Funding (self): Roche, Pfizer, Ono Pharmaceutical, Takeda. M-J. Ahn: Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca, Merck, Sharp & Dohme, Ono Pharmaceutical, Lilly, Roche; Advisory / Consultancy: Alpha Pharmaceutical, Takeda. S.S. Ramalingam: Honoraria (self), Advisory / Consultancy: AstraZeneca, Amgen, Bristol-Myers Squibb, Merck, Roche/Genentech, Loxo, Nektar, Tesaro; Research grant / Funding (institution): AstraZeneca, Amgen, Bristol-Myers Squibb, Merck, Tesaro, Advaxis, Takeda. S-W. Kim: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca. F.A. Shepherd: Advisory / Consultancy, Research grant / Funding (institution), Shareholder / Stockholder / Stock options: AstraZeneca. J. Laskin: Research grant / Funding (institution): AstraZeneca, Roche, Boehringer Ingelheim, Pfizer; Honoraria (self): AstraZeneca, Roche, Pfizer. H. Akamatsu: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Honoraria (institution): Chugai; Honoraria (self), Honoraria (institution), Advisory / Consultancy: Pfizer; Honoraria (self), Honoraria (institution): Boehringer Ingelheim. W-C. Su: Travel / Accommodation / Expenses: Bristol-Myers Squibb; Travel / Accommodation / Expenses: Boehringer Ingelheim. T. John: Advisory / Consultancy: Roche, Bristol-Myers Squibb, Merck, Ignyta, AstraZeneca, Takeda, Boehringer Ingelheim, Pfizer. M. Sebastian: Honoraria (self), Honoraria (institution), Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca, Roche, Novartis; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer, Boehringer Ingelheim, Celgene, Takeda, Bristol-Myers Squibb, MSD; Honoraria (self), Advisory / Consultancy: Lilly. H. Mann: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. M. Miranda: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. G. Laus: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. Y. Rukazenkov: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. V. Papadimitrakopoulou: Honoraria (self): F Hoffman-La Roche; Advisory / Consultancy: Nektar Therapeutics, AstraZeneca Pharmaceuticals, Arrys Therapeutics, Merck&Co, LOXO Oncology, Araxes Pharma, F.Hoffman-LaRoche Ltd, Janssen Research Foundation, Bristol-Myers Squibb, Clovis Oncology, Eli Lilly &Co, Novartis Pharmaceuticals Corp. Takeda ; Research grant / Funding (institution): Eli Lilly &Co, Novartis, Merck, AstraZeneca Pharmaceuticals, F Hoffman-La Roche, Nektar Therapeutics, Janssen, Bristol-Myers Squibb, Checkmate, Incyte. All other authors have declared no conflicts of interest.